Twitter discourse around competitive cycling and sports-related concussion - Hardwicke, J.; Batten, J.; Anderson, E.; Hurst, H. T. (Journal of Science and Cycling, 2022)
The purpose of this study was to explore the cycling community`s online interactions with sports-related concussion within competitive cycling. Through an analysis of twitter data (n=196), this study examined the limited discourse related to the problem of concussion in cycling. The results found overall engagement and awareness of concussion in cycling was low but has been increasing year on year from 2008 to 2019. Thematic analysis of the data found three main themes within the online cycling community on Twitter: 1) Increasing awareness of concussion as a problem for the sport 2) A narrative of apathy in policy by governing bodies and 3) The need for better education as a result of misperceptions of concussion. Overall, these findings contribute to the limited research in the field of concussion in competitive cycling and outline the utility of social media as a platform to disseminate educational resources around the safe management of concussion in the sport.